Sex and slaughter in the tent of Jael: a cultural history of a biblical story - Conway, Colleen M. (Oxford University Press, 2017)
"This book traces the retelling of the biblical story from Judges 4-5 in ancient retellings of the Bible, visual art, poems, plays, and novels. The books shows how these cultural productions of an old biblical story intersect with broader conversations about the often conflicted, and sometimes violent, relationship between women and men"--